O professor que ensina matemática formado em ambientes virtuais de aprendizagem à distância - Gambarra, Julio Robson Azevedo [UNESP] (2015)
The study addressed prospective mathematics teacher education for primary education in virtual environments. The research was guided by the following question: What aspects could be related to mathematics education of prospective teachers who got their degree through distance courses? Addressing this question meant: analyzing the pedagogical projects of the courses; investigating the subject matter of these courses with respect to the mathematical content and its teaching; considering the teacher educators (classroom tutor, virtual tutor, discipline advisor, class advisor) and the criteria used for hiring them; considering the profiles of students attending these courses; and considering the available technology and how it was integrated in the educational practice. The overall objective was to investigate how mathematics was approached in distance undergraduate courses in Pedagogy. The locus of the research was made up by six Centers for Classroom Support (PAP) and two Public Distance Education Programs, located in six cities in São Paulo State, with different characteristics of the population regarding the number of inhabitants and the geographical location. Data analysis was based on content analysis theory meaning that the units of analysis were constructed from the context units and register units. This converged towards two categories of analysis: an overview of the prospective teachers and a overview of the teacher educators. These categories were discussed with reference to literature on teacher education and distance education. In general, this research brings contributions to teacher educators working in distance courses offered prospective teachers who teach mathematics to the early years of elementary school. It also provides indications for the establishment of public policies for teachers distance...